The Relationship Between Gender and Students' Knowledge and Attitudes Towards Healthy Snack Selection in Semarang City Public Elementary Schools - Mulyawati, Isti; Zulfa, Nely; Sudrajat, Agus (Journal of Biomedical Sciences and Health, 2026)
Background: The habit of eating snacks at school is part of the diet of elementary school students who need attention related to their nutritional quality. Knowledge and attitude are often considered determining factors in  choosing  healthy  snacks.  Objective:  This  study aims  to  analyze the relationship  between gender  and  students'  knowledge  and  attitudes  towards  choosing  healthy snacks  at  Semarang  City  State  Elementary  School.  Methods:  Quantitative  study  with  cross- sectional design. The sample consisted of 74 students taken from 21 State Elementary Schools in Semarang  City  using  quota  sampling  techniques.  Data  was  collected  through  a structured questionnaire and  analyzed  using  Chi-Square statistical  tests.  Results:  The univariate  analysis showed that the majority of respondents were female (59.5%), had good knowledge (89.2%), and had good attitudes (41.9%). The results of the bivariate analysis showed no relationship between gender  and knowledge of  healthy snack  selection  (p  value=  1.00)  and  no  relationship between gender and attitudes towards healthy snack selection (p value = 0.196).  Conclusion: Gender is not  a  distinguishing  factor  in students'  knowledge and  attitudes  towards healthy snacks.  This suggests  that  school  health  interventions  should  focus  more  on  strengthening  the  physical environment and the availability of healthy snacks in schools, regardless of gender.